Designing a Content-based Unit Following Contrastive Rhetoric Analysis to Foster Law Students’ Legal Academic Writing Competence - NOUAR, Hanene; BOUKEZZOULA, Mohammed (Journal of Human Sciences, 2025)
The paper sought to achieve two aims. First, to identify the most problematic structural and cultural patterns that could challenge Algerian law students, particularly in achieving competency in English legal academic writing. Second, to develop a content-based unit designed to foster students’ legal academic writing competence through integrating language and content specific to legal studies, namely international property law. To achieve the first aim, a corpus-based analysis of legal articles, book chapters and study materials in Arabic and English pertaining to the chosen area was carried out following the principles of contrastive rhetoric. The analysis employed LancsBox software alongside qualitative efforts. The findings revealed major structural and cultural patterns that may cause difficulty to law students when producing English legal writing: syllogism, reading culture, collocations, passive voice, and text structures. To fulfil the second aim, the paper proposed a teaching unit following the principles of Content-based Instruction (CBI).